Exploring University Students’ Experiences and Perceptions of Breakout Rooms in Online Classes - Farooq, Mariam; Wilson, Jay (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2025)
This research focuses on the use of breakout rooms in online classes at a private university in Saskatchewan, Canada. It aims to explore factors that contribute to successful collaborative graduate student learning experiences and identify challenges students face during peer-to-peer interactions in breakout rooms. A qualitative research approach was employed and data were collected through a qualitative survey and focus group discussion. The survey was distributed to graduate students in three unique online courses within the college of education at the university. The findings highlight a variety of breakout room activities, ranging from open-ended discussions to problem-solving exercises facilitated by collaborative tools such as shared documents and Padlet. The students expressed a preference for activities that were simpler and more accessible, which fostered teamwork and facilitated the exchange of ideas among group members. The challenges that students mentioned dealt with the non-availability of written instructions for activities, unequal participation or dominance by group members, and potential conflicts arising from differing opinions. Recommendations include further exploration of innovative tools to enhance virtual collaboration, comparative studies across different academic levels, and investigations into the long-term impacts of breakout room usage on student learning outcomes.